2018
DOI: 10.1177/0957650918820795
|View full text |Cite
|
Sign up to set email alerts
|

A review of prewhirl regulation by inlet guide vanes for compressor and pump

Abstract: To achieve the energy conservation and sustainable development, the prewhirl regulation by inlet guide vanes is proposed and rapidly developed for the compressor and pump. The inlet guide vanes change the flow pattern at the impeller inlet especially the velocity circulation, and then influence the performance of compressor and pump. This paper presents and discusses researches on the prewhirl regulation by inlet guide vanes. Researches include mechanism analysis of prewhirl regulation, experimental and numeri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…Inlet guide vane installation is a common technique to control the fluid circulation and pressure ratio at the inlet of a turbomachine. This method was initially carried out in compressors and fans and was recently applied to centrifugal pumps to regulate fluid pre-swirl at the inlet [6]. Tan et al [7] studied the effect of an adjustable inlet guide vane for the pre-swirl regulation of a single-stage centrifugal pump and obtained a higher efficiency and head at the design point at an angle of 24 • .…”
Section: Introductionmentioning
confidence: 99%
“…Inlet guide vane installation is a common technique to control the fluid circulation and pressure ratio at the inlet of a turbomachine. This method was initially carried out in compressors and fans and was recently applied to centrifugal pumps to regulate fluid pre-swirl at the inlet [6]. Tan et al [7] studied the effect of an adjustable inlet guide vane for the pre-swirl regulation of a single-stage centrifugal pump and obtained a higher efficiency and head at the design point at an angle of 24 • .…”
Section: Introductionmentioning
confidence: 99%
“…Variable inlet guide vanes (VIGVs) are widely used in axial-flow compressor and other fluid-machines [1][2][3] to provide the requested flow angle into downstream rotor to improve the compressor efficiency and stall margin at off-design conditions. 4,5 Research indicated that as the stagger angle increases the VIGV gradually comes into the high incidence operation conditions and the leading edge velocity spike induced flow separation arises leading to the rapid increase of losslevel, 6,7 which can cause considerable reduction of compressor efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…The prewhirl regulation by IGVs is an effective means of improving the efficiency and operation stability of compressors and fans. Liu et al 16 reviewed the researches on the prewhirl regulation by IGVs for compressors and pumps and the influence of their geometry on the performance. Prewhirl has an obvious impact on pumps energy performance over ranges of flow rates, 17 and the amplitudes of pressure fluctuations seem to lessen at the blade leading edge 18 .…”
Section: Introductionmentioning
confidence: 99%